Er3+- Doped ZnO Nanospheres with Enhanced Upconversion Photoluminescence Produced through Sonochemical Synthesis - Geng, Jun; Song, Guang-Hui; Zhu, Jun-Jie (Current Topics and Emerging Issues in Materials Sciences Vol. 2, 2023)
The photoluminescence and upconversion photoluminescence properties of the asprepared -doped nanospheres were investigated, and the results showed enhanced emission due to effective doping. The formation mechanism of these nanocrystals is connected with the sonochemical effect of ultrasound irradiation. The mechanism of the formation of ZnO nanospheres is probably related to the coordination of Zn^(2+) and TEA to form Zn-TEA complex, the dissociation of the complex under sonication and PEGmodified formation of ZnO nanospheres. The as-prepared Er3+ doped ZnO nanospheres show enhanced photoluminescence and upconversion photoluminescence properties compared with pure ZnO. Higher upconversion photoluminescence emissions of the -doped nanocrystals were observed, which suggests that the ions have been incorporated inside the crystalline grains.